THE RELATIONSHIP BETWEEN STUDENTS’ MATHEMATICS ATTITUDE AND THEIR MATHEMATICAL THINKING - Hasniza Ibrahim,; Norshahira Isa, (Journal of Islamic, Social, Economics and Development, 2023)
This research aims to describe students’ mathematical thinking based on their attitude towards mathematics. In addition, this study also aims to investigate the relationship between students’ mathematics attitude and their mathematical thinking and to know how much influence mathematics attitude among the students with their mathematical thinking. There are two indicators of students’ mathematics attitude which were used in this study, namely Affective Engagement which means emotions or thoughts toward mathematics and Cognitive Engagement which defines as the judgements and beliefs about mathematics. This study employed a descriptive research design and 75 Form Four students from a public school in Segamat, Johor, Malaysia have been chosen as the sample of this study. A Mathematical Thinking Test (MTT) and Mathematics Attitude Questionnaire were used as the instruments in this study to collect the data. Based on the finding of this research, generally, there is a positive correlation between students’ mathematics attitude and mathematical thinking skill. However, according to the Pearson Correlation test results, students’ attitude towards mathematics has little influence on their mathematical thinking ability.